Management of Ureterolithiasis in a Patient with Crossed Unfused Renal Ectopia - Koichi Kodama; Yasukazu Takase; Hiroki Tatsu (Case Reports in Urology)
Crossed renal ectopia is a rare congenital anomaly in which both kidneys are situated on one side and fused together in 85%–90% of cases. The management of urinary calculi in patients with crossed renal ectopia continues to pose challenges to urologists because the aberrant anatomy may make access and clearance of the calculi more difficult to accomplish. Here, we report a case of inferior crossed renal ectopia, without fusion, and a ureteral stone in which the patient was treated successfully by extracorporeal shock wave lithotripsy.